The Effect of Job Satisfaction to Organizational Citizenship Behavior (OCB) Mediated by Organizational Commitment - Fitrio, Tomy; Apriansyah, Roky; Utami, Sabrina; Yaspita, Hasanah (International Journal of Scientific Research and Management (IJSRM), 2019)
This research aimed to find out the effect of job satisfaction to organizational citizenship behavior, organizational commitment to organizational citizenship behavior, and job satisfaction to organizational citizenship behavior mediated by organizational commitment at Economics College of Indragiri Rengat. The number of the sample in this research is 34, filled by the lectures of Economics College of Indragiri Rengat. This research used Saturated Sampling methods, where all population as the sample of this research. To collect all the data, this research used Closed Questionnaires techniques. This research used Likert Scale as data measurement techniques. This research used Structural Equation Modeling (SEM) as data analysis techniques operated by Smart PLS 3.0 application. This research shows that: (1) job satisfaction has a positive and significant effect to organizational citizenship behavior (OCB), (2) organizational commitment has a positive and significant effect to organizational citizenship behavior (OCB), (3) job satisfaction has a positive and significant effect to organizational citizenship behavior (OCB), (4) organizational commitment mediated the effect between job satisfaction to organizational citizenship behavior (OCB) positively and significantly.